Beat-induced fluctuations in auditory cortical beta-band activity: using EEG to measure age-related changes - Cirelli, Laura K.; Bosnyak, Dan; Manning, Fiona C.; Spinelli, Christina; Marie, Céline; Fujioka, Takako; Ghahremani, Ayda; Trainor, Laurel J. (Frontiers in Psychology, 2014)
People readily extract regularity in rhythmic auditory patterns, enabling prediction of the onset of the next beat. Recent magnetoencephalography (MEG) research suggests that such prediction is reflected by the entrainment of oscillatory networks in the brain to the tempo of the sequence. In particular, induced beta-band oscillatory activity from auditory cortex decreases after each beat onset and rebounds prior to the onset of the next beat across tempi in a predictive manner. The objective of the present study was to examine the development of such oscillatory activity by comparing electroencephalography (EEG) measures of beta-band fluctuations in 7-year-old children to adults. EEG was recorded while participants listened passively to isochronous tone sequences at three tempi (390, 585, and 780ms for onset-to-onset interval). In adults, induced power in the high beta-band (20-25 Hz) decreased after each tone onset and rebounded prior to the onset of the next tone across tempo conditions, consistent with MEG findings. In children, a similar pattern was measured in the two slower tempo conditions, but was weaker in the fastest condition. The results indicate that the beta-band timing network works similarly in children, although there are age-related changes in consistency and the tempo range over which it operates.